On the power performance of a wave energy converter with a direct mechanical drive power take-off system controlled by latching. (May 2021) - Shadman, Milad; Guarniz Avalos, Gustavo Omar; Estefen, Segen F.
Abstract: Several latching control strategies have been proposed to improve the power performance of wave energy converters (WECs). However, the benefits and challenges vary for different WECs and PTO systems. This paper addresses the power performance of a specific direct mechanical-drive power take-off (DMDPTO) system considering the application of a non-predictive latching control. The WEC is a heaving point absorber (PA) that consists of a cylindrical buoy and a bottom-mounted support structure. A pulley converts the vertical motion of the buoy into rotational motion, and a freewheel system rectifies the rotation direction for the power generation. A speed multiplier amplifies the velocity delivered by the buoy to drive a flywheel, which is rigidly connected to the electrical generator. A time-domain model is developed to simulate the interaction of the wave-buoy-DMDPTO in each time interval calculating hydrodynamic and electro-mechanical forces. An exhaustive optimization strategy is applied to maximize power production, optimizing the DMDPTO parameters. The sensitivity of power production to the wave height and wave period are presented considering the generator's operational limit. Additionally, the capture width ratio and peak-to-average power ratio are calculated for the controlled PA, and the results are compared to the control-free WEC and linear PTO systems. Highlights: The power performance of a DMDPTO applying a latching control. 282% and 23% of CWR increase compared to control-free and linear PTO, respectively. Power increase strictly depends on the maximum operational speed of the generator. Up to 300% less buoy-DMDPTO engagement-disengagement using latching. Significant improvement in power smoothness comparing to the linear PTO.